Synthesis and Photophysical Properties of New Heteronuclear Rhenium(I)-Ytterbium(III) Coordination Complex - Bobukhov, Dmytro; Shtemenko, Olexandr (Видавництво Львівської політехніки, 2013)
New heteronuclear Re(I)–Yb(III) molecular square having Yb(PMFP)3 (where PMFP = 1-phenyl-3- methyl-4-formyl-2-pyrazolin-5-one) and fac-Re(CO)3Br as corners, and 4,4 -bipyridine (4,4 -bpy) as the bridging ligand have been synthesized and characterized. In the near-infrared region Re–Yb complex exhibits strong sensitized emission with the maximum at 977 nm.
Keywords: rhenium carbonyl; heteronuclear complex; luminescence; molecular square; lanthanide; ytterbium; emission; sensitizer